UTERINE INVAGINATION IN A CROSS BRED COW-A CASE REPORT - Prabaharan, V; Krishnakumar, K; Chandrahasan, C (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
An unusual case of invagination of uterine horn was treated successfully in a Holstein Friesian cross bred cow and it has been put on record.